(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The aim of the research is to test the effect of knowledge sharing in achieving organizational success at the University of Sumer, and the research problem crystallizes the need for the university, being one of the young universities, to enhance and improve the processes of knowledge sharing to enhance the efficiency and effectiveness of its educational operations and activities in order to achieve its goals to keep pace with and join large universities, whether local or even global. To answer the research question (what is the impact of knowledge sharing on achieving organizational success), The researcher designed a questionnaire consisting of (22) paragraphs for collecting primary data from the research sample Consisting of (63) members of the university professors and staff, The researcher used a set of statistical tools, including "Cronbach’s alpha, Kolmogorov-Smirnov, arithmetic mean, standard deviation", Spearman correlation coefficient., " The research reached a number of conclusions, the most important of which are that process of knowledge sharing has had a clear impact on the University’s success , This reflects the keenness of the university administration and its interest in the process of knowledge sharing to achieve efficiency and effectiveness in its activities and operations", The study recommended The need for university administrations to develop various policies and programs that enhance the process of knowledge sharing among all its faculties and departments